Novel Hybrid of Typical Enteropathogenic Escherichia coli and Shiga-Toxin-Producing E. coli (tEPEC/STEC) Emerging From Pet Birds - Gioia-Di Chiacchio, Rosely Martins; Cunha, Marcos Paulo Vieira; de Sá, Lilian Rose Marques; Davies, Yamê Minieiro; Pereira, Camila Bueno Pacheco; Martins, Fernando Henrique; Munhoz, Danielle Dias; Abe, Cecilia Mari; Franzolin, Marcia Regina; dos Santos, Luis Fernando; Guth, Beatriz Ernestina Cabilio; Elias, Waldir Pereira; et al. (Frontiers in Microbiology, 2018)
Exotic psittacine birds have been implicated as reservoir of diarrheagenic Escherichia coli (E. coli), including enteropathogenic E. coli (EPEC) and Shiga-toxin producing E. coli (STEC). Here, we present a genotypic and phenotypic characterization of typical EPEC/STEC hybrid strains isolated from exotic psittacine birds. The strains were positive for eae, bfpA, and stx2f genes, belonged to serotype O137:H6 and ST2678. Two strains were subject to whole genome sequencing, confirming the presence of the virulence factors of both E. coli pathotypes. Phenotypical in vitro tests confirmed their ability to adhere to HeLa cells and cause cytotoxicity to Vero cells. The rabbit ileal loop assays showed the attaching and effacing lesion, in addition to inflammatory process and overproduction of intestinal mucus. This is the first report of hybrid typical EPEC/STEC (O137:H6/ST2678) strains isolated from companion psittacine birds and the results suggest zoonotic risks.